Affective, normative, and continuance commitment levels across cultures: A meta-analysis - Meyer, John; Stanley, D.; Jackson, T.; McInnis, K.; Maltin, E.; Sheppard, L. (Academic Press, 2012)
With increasing globalization of business and diversity within the workplace, there has been growing interest in cultural differences in employee commitment. We used meta-analysis to compute mean levels of affective (AC; K=966, N=433,129), continuance (CC; K=428, N=199,831), and normative (NC; K=336, N=133,277) organizational commitment for as many as 54 countries and nine geographic regions, and used cultural values/practices from the Hofstede (2001), Schwartz (2006), and GLOBE (House, Hanges, Javidan, Dorfman, & Gupta, 2004) taxonomies to account for observed variance. We found that cultural values/practices explained the greatest amount of variance in NC, followed by AC; they did not explain variance in CC. When economic indicators were controlled, Schwartz's value orientations accounted for the most incremental variance, particularly in NC. We provide country-level normative data for the three components of commitment and discuss the implications of our findings for multi-national organizations as well as for companies employing individuals with varying cultural backgrounds.